Improvement of the Mechanical Behavior of an Environmental Concrete Based on Demolished Concrete Waste and Silica Fume - Oussama Kessal; Larbi Belgraa; Noura Djebri; Soumia Salah; Zineb Allal (Salehan Institute of Higher Education, 2022)
The universal need to conserve resources, protect the environment, and use energy efficiently must necessarily be felt in the field of concrete technology. In Algeria, the rapid growth in the construction sector and the difficulties in setting up new quarries make it necessary to find effective alternatives to use them as building materials. The recycling of construction and demolition waste as a source of aggregates for the production of concrete has attracted growing interest from the construction industry. In this context, this work is a part of the approach to provide answers to concerns about the lack of aggregates for concrete. It also aims to develop the inert fraction of demolition materials, mainly concrete construction demolition waste (C&D), as a source of aggregates for the manufacture of new hydraulic concrete based on recycled aggregates. This experimental study presents the results of physical and mechanical characterizations of natural and recycled aggregates, as well as their influence on the properties of fresh and hardened concrete. The characterization of the materials used has shown that the recycled aggregates have heterogeneity, a high-water absorption capacity, and medium-quality hardness. However, the limits prescribed by the standards in force do not disqualify these materials from use for application as recycled aggregate concrete. The effect of silica fume and superplasticizer percentage on the mechanical and physical properties of concrete with NA and RA was analyzed and optimized using full-factorial design methodology. The results obtained from the present study show acceptable mechanical, compressive, and flexural strengths of concrete based on recycled aggregates by using Superplasticizer and 5% of silica fume, compared to those with natural aggregates. The results of the water absorption as well as the UPV confirm the positive effect of the use of superplasticizer and silica fume on the physical and mechanical behavior of concrete with recycled aggregates. Factorial design analysis shows that the developed mathematical models can be used to predict the physical and mechanical properties of concrete with RAC, superplasticizer, and silica fume. Doi: 10.28991/CEJ-2022-08-02-04 Full Text: PDF